Verbal coping of coaches in competition: Differences depending on emotional intelligence and self-determined motivation - Grijalbo, C.; Martínez-Gallego, R.; Guzmán, J. F. (International Journal of Sports Science & Coaching, 2022)
In this study we analysed the differences in verbal behaviour of coaches during matches. A total of 9739 verbal behaviours issued by 26 male handball coaches in 26 matches, 1 for each coach, were classified into the categories established by the Coach Analysis and Intervention System (CAIS). These behaviours in turn were grouped according to the type of coping expressed by the coach (task-oriented, emotional positive and emotional negative). Coaches were then classified into high or low emotional intelligence, and high or low self-determined motivation, using the mean of these scores. Differences in verbal behaviour percentages were analysed by Chi-square based on coach membership in groups of emotional intelligence and self-determined motivation. Coaches with greater self-determined motivation and emotional intelligence used more verbal behaviours showing positive emotional coping. Results are discussed based on the impact on the health and performance of athletes, as well as possible interventions to improve the leadership of the coach in a match situation.